2010
DOI: 10.1016/j.bbamem.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte morphological states, phases, transitions and trajectories

Abstract: Morphological response (MR) of red blood cells represents a triphasic sequence of spontaneously occurring shape transformation between different shape states upon transfer the cells into isotonic sucrose solution in the order: S(0) (initial discoid shape in physiological saline)-->S(1) (echinocytic shape at the beginning of MR, phase 1)-->S(2) (intermediate discoid shape, phase 2)-->S(3) (final stomatocytic shape, phase 3). In this paper, the dynamics of cell shape changes was investigated by non-invasive ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 68 publications
3
27
0
1
Order By: Relevance
“…Phospholipids missing from the outer membrane bilayer of RBCs can cause expansion of the inner leaflet relative to the outer leaflet, resulting in membrane shape transformations. 50,67 Our observation of changed erythrocyte shape is partly consistent with the findings of Han et al, 35 ie, that the surface charge on NPs is the dominant factor influencing their hemocompatibility, but the findings of our study suggest that the sizes of NPs and their agglomerates also play an important role. In addition, Asharani et al 34 reported that the low degree of surface deposition of NPs on the membrane of RBCs can be accompanied by significant alterations in membrane topography.…”
Section: Mlvs After Incubation In Np Suspensionssupporting
confidence: 82%
“…Phospholipids missing from the outer membrane bilayer of RBCs can cause expansion of the inner leaflet relative to the outer leaflet, resulting in membrane shape transformations. 50,67 Our observation of changed erythrocyte shape is partly consistent with the findings of Han et al, 35 ie, that the surface charge on NPs is the dominant factor influencing their hemocompatibility, but the findings of our study suggest that the sizes of NPs and their agglomerates also play an important role. In addition, Asharani et al 34 reported that the low degree of surface deposition of NPs on the membrane of RBCs can be accompanied by significant alterations in membrane topography.…”
Section: Mlvs After Incubation In Np Suspensionssupporting
confidence: 82%
“…This may strongly support the low pHi, observed in RBCs tending to a stomatocytic transformation, and the caspase 3 activation always linked to an acidic pHi [20, 38], both conditions observed in the presence of CPZ. This caspase 3 is a zymogen maintained in an inactive structural conformation, by an Asp-Asp-Asp regulatory tripeptide named “safety-catch” [21].…”
Section: Discussionsupporting
confidence: 57%
“…But it appears quite surprising if it is evaluated that PB3 is highly expressed in the RBC membrane just where the drug is mostly concentrated. The action of CPZ on the membrane has been widely demonstrated by the observation of the induction of stomatocytic transformation, always linked to a decrease in cytoplasmic pH (pHi) [20, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that acute lowering of the ZP can result in an acute increase in endothelial cell permeability and acute alteration in RBC morphology from dispersed biconcave discs to adherent rouleaux formations [248], echinocyte, stomatocyte, acanthocyte, and spherocyte transformations [113,[293][294][295][296][297][298][299][300][301][302][303][304][305][306], with consequent elevation in blood viscosity, elevated resistance to microvascular blood flow, diminished oxygen transport, and diminished oxygen delivery. CO 2 overload is a secondary inevitable consequence of the acute colloidal instability of our blood induced by the ZP-lowering, polycationic surfactant stress.…”
Section: Discussionmentioning
confidence: 99%